2018
DOI: 10.1111/his.13664
|View full text |Cite
|
Sign up to set email alerts
|

Sebaceous adenocarcinomas of the major salivary glands: a clinicopathological analysis of 10 cases

Abstract: The sebaceous adenocarcinoma of salivary glands is rare and may show an unfavourable outcome; therefore, its correct diagnosis may be challenging. For this reason, immunohistochemical studies, including adipophilin in particular, constitute an important diagnostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
0
15
1
Order By: Relevance
“…2,18,19 Additionally, because of their differentiation, sebaceous adenocarcinoma cells of the major salivary glands are consistently positive for adipophilin, which is a diagnostic tool for this disease. 13,20,21 In a previous study, we observed the coexpression of FASN and cyclooxygenase-2 (COX-2) in AM and AC. Since these proteins can be coexpressed in lipid droplets, we offered a hypothesis stating that lipid droplets are present in these tumors and hence play roles in tumorigenesis, which needs to be further explored.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…2,18,19 Additionally, because of their differentiation, sebaceous adenocarcinoma cells of the major salivary glands are consistently positive for adipophilin, which is a diagnostic tool for this disease. 13,20,21 In a previous study, we observed the coexpression of FASN and cyclooxygenase-2 (COX-2) in AM and AC. Since these proteins can be coexpressed in lipid droplets, we offered a hypothesis stating that lipid droplets are present in these tumors and hence play roles in tumorigenesis, which needs to be further explored.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, the authors of this previous study suggested that there is a relationship between upregulated lipogenesis and high‐grade transformation and that lipid droplets play roles in sustaining cell proliferation 2,18,19 . Additionally, because of their differentiation, sebaceous adenocarcinoma cells of the major salivary glands are consistently positive for adipophilin, which is a diagnostic tool for this disease 13,20,21 …”
Section: Discussionmentioning
confidence: 96%
“…Most, if not all, of the few cases reported appear to have arisen de novo and not from a pre-existing sebaceous adenoma [25,27]. A recent study of ten new cases of sebaceous adenocarcinoma also supports that they arise de novo as none of the ten reported cases had arisen from a pre-existing sebaceous adenoma [28].…”
Section: Sebaceous Adenomamentioning
confidence: 90%
“…Radical or selective neck dissection should be performed, to evaluate lymph node metastasis. Adjunctive radiotherapy or chemotherapy are necessary, depending on the stage of the tumor at the time of presentation, or when the surgical margins are diffused [1,3,6,8,9,11,13,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…More rare is distant metastasis to the lung, pleura, liver, brain, pericardium, lips, ethmoid sinus and skull. The overall mortality rate is 5 -10%, while in cases of metastasis the rate may go up to 25% and up to 41% in cases where the duration of symptoms lasts more than six months [1,3,8,9,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%